“ABDULLA AVLONIY FAOLIYATI MEN UCHUN YUKSAK NAMUNA” - Nizamova Malika Ravshan qizi (Journals Park Publishing, 2023)
Adib's rich pedagogical heritage consists in promoting national pedagogical works on education among students.
Keywords: school, science, ethics, upbringing, education.